IMPLEMENTATION OF FACE-TO-FACE LEARNING (Analysis of Readiness of Parents, Learners and Education Units in Bengkulu city) - Emilda Sulasmi (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This article discusses the application of face-to-face learning after implementing large-scale social restrictions and the Enactment of Community Activity Restrictions (PPKM) of various levels as strategies for preventing and handling the spread of Covid-19. The analysis in this article focuses on the readiness of learners and educational institutions in terms of learning policy and facilities, and infrastructure. Qualitative methods are used in this research with a field approach. Data sources are obtained from elementary, middle, and high school students and principals, and teachers in Bengkulu City who are selected based on research focus needs. The results showed that students were very ready to follow face-to-face learning. However, gradually vaccinations will be carried out, the need for face-to-face is felt to be very important because many students have never met classmates and teachers who teach, especially for students in grades I and 2 elementary schools, class VII and VIII junior high, and X and XI high school. In addition, the school also stated that it is very ready for face-to-face learning by preparing all supporting devices related to health protocols and efforts to prevent the spread of Covid-19 by designing learning patterns in terms of lesson hours, classrooms, and other facilities. Students and educational institutions found several things related to education about the importance of vaccination and limited lesson hours related to the obstacles faced. They increased teacher activity in carrying out teaching tasks